THE RELATIONSHIP BETWEEN KNOWLEDGE ABOUT HIV/AIDS AND ADOLESCENT SEXUAL BEHAVIOR IN THE WORKING AREA OF PATI I PUBLIC HEALTH CENTER - Yuli Yanti; Feri Catur Yuliani; Yeni Rusyani; Ratna (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
HIV/AIDS remains a global health problem, including in Indonesia, with a significant impact on adolescents as a high-risk group. Adequate knowledge about HIV/AIDS is expected to foster healthier sexual behaviors, thereby minimizing the risk of transmission. The increasing prevalence of risky sexual behavior among adolescents can contribute to high rates of HIV/AIDS transmission. to determine the relationship between the level of knowledge about HIV/AIDS and adolescent sexual behavior. This research is quantitative with a correlational design using a cross-sectional approach. The study population was adolescents aged 15–19 years in the Pati I Community Health Center working area, with a sample of 100 respondents selected using proportional random sampling. The research instrument was a questionnaire that had been tested for validity and reliability, including 10 questions for the HIV/AIDS knowledge variable and 10 questions for the sexual behavior variable. Data analysis was performed univariately to observe the frequency distribution and bivariately using the Spearman correlation test. showed that most respondents had a level of knowledge about HIV/AIDS in the category of less (49%), sufficient (28%), and good (23%). As many as 55% of respondents were classified as having risky sexual behavior, with forms of behavior varying from holding hands to penetrative sexual intercourse. The results of the bivariate test showed a significant relationship between the level of knowledge about HIV/AIDS and adolescent sexual behavior (p-value = 0.031) with a weak positive correlation (r = 0.215). Conclusion: There is a significant relationship with a positive direction between knowledge about HIV/AIDS and adolescent sexual behavior.